A influência das atividades de marketing na performance de exportação em países emergentes: um estudo sobre micro e pequenas empresas brasileiras - Cunha, Reynaldo Dannecker (2012)
This study analyzes the influence of marketing activities in the internationalization process of micro and small enterprises (MSEs) in emerging countries, focusing on export operations carried out by Brazilian companies. The overall objective is to analyze these activities and check its impact on export performance of MSEs. The specific objectives involve the evaluation of adaptation-standardization strategies, considering the marketing mix (product, price, communication and distribution) on foreign markets; the export performance and its relevance to their business success. To that end, it was developed a conceptual framework that examines company and products characteristics, entrepreneurial marketing and how they influence the marketing activities in the export process. The model is based on a conceptual analysis on export marketing strategy (EMS) and export performance developed by Cavusgil and Zou (1994). In order to understand the context, a comprehensive theoretical review evaluated theories of globalization, marketing and the historical performance of micro and small enterprises in Brazilian exportation. To test the hypothesis a survey was performed with 173 MSEs available at SEBRAE, ABICALÇADOS and Serasa Experian databases; data were analyzed using descriptive and multivariate statistics by structural equation modeling (SEM). It was possible to detect the importance of EMS in the export performance of MSEs studied, mainly by adapting the price to the target market, making it more competitive. It was identified the critical role of international competence of the company for greater success in exporting, as well as the indirect influence of entrepreneurial marketing in export performance, through the impact on EMS. As contributions, the development of the conceptual model adapted to MSEs improves Cavusgil and Zou (1994) model, because this has been tested only in large companies, filling therefore an empirical gap. In addition, studying the export performance of MSEs is aligned with the importance of such company for the Brazilian economy, and the diagnosis on export performance of the same, from economic and strategic criteria, not only contributes to managerial decisions, but to government policies.